Minimum Randić Index of Trees with Fixed Total Domination Number - Ayu Ameliatul Shahilah Ahmad Jamri; Fateme Movahedi; Roslan Hasni; Rudrusamy Gobithaasan; Mohammad Hadi Akhbari (Mathematics, 2022)
The Randić index is among the most famous degree-based topological indices in chemical graph theory. It was introduced due to its application in modeling the properties of certain molecular structures and has been extensively studied. In this paper, we study the lower bound of the Randić index of trees in terms of the order and the total domination number. Finally, trees with the minimal Randić index are characterized.